UJI LENTUR BALOK BETON BERTULANG BENTANG 60 CM DENGAN BAHAN SPLIT PALU DAN PASIR MAHAKAM - USMAN, ERWINSYAH (KURVA S JURNAL MAHASISWA, 2017)
Final Faculty of Civil Engineering Department of the University of August 17, 1945Samarinda.Normal concrete is concrete beams that have a weight of 2200 - 2500 kg / m3 usingnatural aggregates were broken or without broken.Concrete Beams Using a mixture of concrete reinforcement steel reinforcement plusseries ,. The reinforcement in the concrete prevents cracks making the concrete more ductile thanordinary concrete. The purpose of this study to determine the comparative value of the resultingflexural strength of normal concrete beams and concrete beams using reinforcement using coarseaggregate EX. Palu and fine aggregate from Samarinda Mahakam river.This study using the test method (Indonesian National Standard) SNI 4431: 2011 wereperformed in the laboratory using a maximum size of coarse aggregate is 30 mm. The sample usedfor normal concrete beams and concrete beams using reinforcing each using 18 samples and thetotal number of samples is 36 samples.From the test results of concrete beam flexural strength of normal at 28 days averagevalue of flexural strength (f'cr) was 43.556 Kg / cmÂ² or 4.356 MPa. Flexural strength testing usingiiia reinforced concrete beam at 28 days the value of the average flexural strength (f'cr) is 92.000 kg/ cm2 or 9.200 MPa.